MULAZAMAH SEBAGAI TRADISI ILMIAH DALAM PEMBELAJARAN ILMU SYAR’I DI PPTQ AR ROYYAN PACITAN - Trisdianto, Hary; Alwi, Itsnaini Muslimati (LPPM STAI Muhammadiyah Probolinggo, 2025)
This study aims to examine the implementation of the mulazamah method as a scholarly tradition in the teaching of Islamic sciences (‘ilm al-shar‘i) at the Tahfidzul Qur’an Islamic Boarding School (PPTQ) Ar-Royyan Pacitan. The mulazamah method, rooted in the classical Islamic scholarly tradition, is a learning system based on close, intensive, and continuous interaction between teacher and student. This research employs a descriptive qualitative approach with data collected through observation, in-depth interviews, and documentation. The findings indicate that mulazamah is a learning method that emphasizes long-term intensive mentorship between students and their teachers. According to the pesantren leadership, the implementation of this method is not merely a pedagogical choice, but part of a broader strategy to produce a generation that excels in knowledge, character, and leadership. Furthermore, the implications of mulazamah have a direct impact on the students’ deep understanding of Islamic sciences, mastery of the Arabic language, character formation, and the emergence of future scholars with strong leadership capabilities. However, several challenges were identified in the implementation of this method, including limited student time, a shortage of mentors, diverse academic backgrounds among students, a lack of awareness regarding the value of mulazamah, and insufficient supporting facilities.